Lives and letters of an immigrant family : the Van Dreveldts' experiences along the Missouri, 1844-1866 - Kronenberg, Kenneth, 1946- (University of Nebraska Press, 1998)
"Anton and Theodor van Dreveldt grew up in Emmerich, Prussia, as the sons of a Catholic priest and his housekeeper - a situation their father tried to disguise by presenting himself as their uncle. As young men, both Anton and Theodor found their lives increasingly troubled. Anton drank heavily, and Theodor's career was jeopardized by his participation in a banned political organization. These troubles, combined with growing Prussian authoritarianism, led to their independent emigrations to the United States, Theodor in 1844 and Anton in 1849." "Theodor, tormented by malaria and financial difficulties, returned to Germany, but Anton and his son Bernhard, who emigrated after Theodor's return, remained. This separation helped produce a remarkable body of correspondence describing the van Dreveldts' often troubled relationships with each other, their homeland, and America. Their letters compare the age-old tribulations of Europe against the promise and challenges of a new country. The van Dreveldts' experience provide a fascinating glimpse into the complexities of immigrant life."--Jacket